Troy Paper - Blast-Furnace Slags - Kenneth Robertson (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
THEREi9 probably less known of this subject than of any other connected with the metallurgy of iron. In all the books that treat of this mattes, there are given analyses of slags, their chemical formulae, the loss of iron, etc. ; but few, if any, give the character of the iron made at the time ; none give analyses and physical characteristics of the ores and limestones used, and they present merely isolated examples from various furnaces, and consequently one is more frequently puzzled than enlightened after reading them. During two years I have had occasion to analyze the slags and many of the pig-irons from two furnaces, and for this article I have made analyses of all the different grades of pig made by them. A